Effectiveness of MGNREGA on Rural Employment in Assam - Navajyoti Gogoi, Salman Hussain (International Journal of Modern Agriculture, 2021)
Mahatma Gandhi National Rural Employment Guarantee Act (MGNREGA) is one of the major employments generating programs to address the unemployment problem in rural India. The act was enacted on 25th August 2005 and came into force on 2nd February 2006. In Assam, this act was introduced in the financial year 2006-07, and as the first phase, it covered only 7 districts of the state. Later it was expanded to all the districts of the state by the financial year 2008-09. The act came with the main objective to ensure livelihood security among the rural mass by providing at least 100 days of job security in every financial year. It is seen that till date the majority of the rural people of Assam directly or indirectly related to agriculture for their livelihood, due to which it createsproblems like disguised and seasonal unemployment. Available literature shows that some extent MGNREGA have got success by reducing unemployment by providing working days to the majority of the unskilled and illiterate people of the state living in rural areas. Based on the secondary data, the present study tries to examine the effectiveness of MGNREGA on employing the rural people of the state, as well as to analyze the various challenges to meet its goal.